Karakterisasi Pembentukan Ko-kristal Tenoksikam-Asam Malat dan Evaluasi Kompresibilitas dan Tabletabilitasnya - Alatas, Fikri; Syahidatul Alamiah, Dzaza; Purnamasari, Nira (JURNAL FARMASI GALENIKA, 2023)
Tenoxicam is a non-steroidal anti-inflammatory drug which has poor compressibility and compactibility. One way to change the compressibility and compactibility of a material is to use co-crystallization techniques The aim of this research is to characterize the formation of co-crystal between tenoxicam and malic acid and evaluate their compressibility and tabletability. Tenoxicam-malic acid co-crystal were prepared using the ultrasound-assisted solution co-crystallisation (USSC) method with the addition of ethanol solvent at the same molar ratio. The USSC result was characterized by polarization microscopy, powder X-ray diffraction, and thermal analysis methods. Evaluation of compressibility and tabletability (tensile strength and elactic recovery) was carried out on tenoxicam-malic acid co-crystal and intact tenoxicam. Characterization of the USSC result indicated the formation of tenoxicam-malic acid co-crystal, which were characterized by crystal habit, powder X-ray diffraction patterns, and DSC thermograms that were specific and different from intact tenoxicam and malic acid. Compressibility evaluation results show that the tenoxicam-malic acid co-crystal is in the good flow properties category, while the intact tenoxicam is in the poor flow properties category. The tensile strength of tenoxicam-malic acid co-crystal is higher than that of intact tenoxicam at the same compression strength (40 kg/cm2). Tenoxicam-malic acid co-crystal showed lower elastic recovery compared to intact tenoxicam. These results can be concluded that tenoxicam-malic acid co-crystals have been successfully prepared using the USSC method and have better compressibility and tabletability than intact tenoxicam.